Identifying of 22q11.2 variations in Chinese patients with development delay - Yuanyuan Zhang; Xiaoliang Liu; Haiming Gao; Rong He; Yanyan Zhao (BMC, 2021)
Abstract Background 22q11.2 variation is a significant genetic factor relating to development delay and/or intellectual disability. However, the prevalence, genetic characteristics and clinical phenotype in Chinese patients are unknown. Methods In total 6034 patients with development delay and/or intellectual disability were screened by multiplex ligation-dependent probe amplification (MLPA) P245 and G-band karyotyping. The positive patients with 22q11.2 imbalance were confirmed by MLPA P250 assay. Results 52 (0.86%) patients were found to carry different levels of 22q11.2 variations, in which 37 cases (71.2%) had heterozygous deletions, whereas 15 (28.8%) had heterogeneous duplications. 34 cases (65.4%) carried typical imbalance from low copy repeat (LCR) 22 A to D. The other cases had atypical variations, relating to LCR22 A-B, LCR22 C-D, LCR22 B-D, LCR22 D-E, LCR22 E-F and LCR22 B-F region. The phenotypes of these 52 patients were variable, including development delay, language delay, facial anomalies, heart defects, psychiatric/behavior problems, epilepsy, periventricular leukomalacia, hearing impairment, growth delay etc. Conclusion These data revealed the prevalence and variability of 22q11.2 genomic imbalance in Chinese patients with development delay and/or intellectual disability. It suggested that genetic detection of 22q11.2 is necessary, especially for the patients with mental retardation and development disorders, which deserves the attention of all pediatricians in their daily work.